Active Noise Control with a Single Nonlinear Control Filter for a Vibrating Plate with Multiple Actuators - MAZUR, Krzysztof; PAWEŁCZYK, Marek (Archives of Acoustics, 2013)
Vibrating plates can be used in Active Noise Control (ANC) applications as active barriers or assecondary sources replacing classical loudspeakers. The system with vibrating plates, especially whennonlinear MFC actuators are used, is nonlinear. The nonlinearity in the system reduces performance ofclassical feedforward ANC with linear control filters systems, because they cannot cope with harmonicsgenerated by the nonlinearity. The performance of the ANC system can be improved by using nonlinearcontrol filters, such as Artificial Neural Networks or Volterra filters.However, when multiple actuators are mounted on a single plate, which is a common practice to provideeffective control of more vibration modes, each actuator should be driven by a dedicated nonlinear controlfilter. This significantly increases computational complexity of the control algorithm, because adaptationof nonlinear control filters is much more computationally demanding than adaptation of linear FIR filters.This paper presents an ANC system with multiple actuators, which are driven with a single nonlinearfilter. To avoid destructive interference of vibrations generated by different actuators the control signal isfiltered by appropriate separate linear filters. The control system is experimentally verified and obtainedresults are reported.